1-(4-((5-chloro-4-((2-(isopropylsulfonyl)phenyl)amino)pyrimidin-2-yl)amino)-3-methoxyphenyl)-3-(2-(dimethylamino)ethyl)imidazolidin-2-one (ZX-42), a novel ALK inhibitor, induces apoptosis and protective autophagy in H2228 cells. (28th June 2020) - Wang, Lijing; Xu, Xiaobo; Liu, Tong; Wang, Junfang; Shen, Jiwei; Guo, Ming; Wu, Yingliang; Zhai, Xin; Zuo, Daiying
Abstract: Objectives: To examine the antiproliferative effects of 1-(4-((5-chloro-4-((2-(isopropylsulfonyl)phenyl)amino)pyrimidin-2-yl)amino)-3-methoxyphenyl)-3-(2-(dimethylamino)ethyl)imidazolidin-2-one (ZX-42) on the echinoderm microtubule-associated protein-4/anaplastic lymphoma kinase fusion gene (EML4-ALK) positive lung cancer cell line H2228 and its underlying mechanism. Methods: The MTT assay was used to study the effect of ZX-42 on H2228 cell growth. Propidium iodide (PI) staining and Western blotting were used to investigate the cell cycle changes. ZX-42-induced cell apoptosis was determined using the Annexin V-FITC/PI (AV/PI) apoptotic assay kit, acridine orange/ethidium bromide (AO/EB) and Hoechst 33258 staining, Rhodamine 123 (Rh 123) fluorescence assay and Western blotting. ZX-42-induced reactive oxygen species (ROS) production was examined by ROS assay kit. Transmission electron microscope, monodansylcadaverine (MDC) staining and the AV/PI apoptotic assay kit were used to demonstrate the relationship between autophagy and apoptosis. Key findings: ZX-42 had good cell viability inhibitory effect on H2228 cells. ZX-42 dramatically inhibited ALK and its downstream pathways. ZX-42 also blocked H2228 cell cycle at G1 phase and then induced apoptosis by activating the mitochondrial pathway. Next, ZX-42 induced the production of ROS, and antioxidant N-acetylcysteine (NAC) reduced ROS production and also decreased apoptotic rates. We also found that ZX-42 induced protective autophagy in H2228 cells. Conclusions: In summary, ZX-42 is a novel ALK inhibitor that significantly inhibits the cell viability of H2228 cells and ultimately induces apoptosis through the mitochondrial pathway, in which autophagy plays a protective role. Therefore, inhibition of autophagy might enhance the anti-cancer effect of ZX-42.